Collaborative exploration and collection of native plant genetic resources as assisted by agrobiodiversity fair - Mainali, Ram P; Karkee, Ajaya; Neupane, Dipesh; Pokhrel, Padma; Thapa, Pradip; Ghimire, Krishna H; Joshi, Bal K; Mishra, Krishna K (Journal of Agriculture and Natural Resources, 2020)
This article describes the agrobiodiversity fair aided exploration and collection expedition of native plant genetic resources in southern Lalitpur, jointly organized by the National Agriculture Genetic Resources Centre (NAGRC) and Group of Helping Hands (SAHAS) Nepal. In-district one-day agrobiodiversity fairs were organized in February and December month of 2019, altogether two times, and these agrobiodiversity fairs were used as a tool to explore plant genetic resources found in Bagmati and Mahankal Rural Municipalities of Lalitpur district. To collect these explored genetic resources during agrobiodiversity fairs, the joint field expedition, key informant survey, diversity rich farmers discussion was used as a collection tool. The present study explored, inventoried, collected and conserved 148 accessions of 44 crop species, the highest number (18 accessions) was of chayote followed by 10 accessions each of soybean, cowpea and maize and 9 accessions of common bean. Collections are generally new and unique. Many landraces, mostly from rice (13 landraces) were identified as extinct from the surveyed areas and few are under extinction mainly due to attraction of farmers to new high yielding varieties. The collected species with orthodox seeds were tested for germination ability and those that passed a minimum of 85% germination, were preserved in seedbank of NAGRC. NAGRC plans to characterize these accessions in the coming seasons depending upon the season of crop growing. The current expedition collected eight species for which mode of propagation is vegetative or those for which seed storage behavior falls under intermediate mode. NAGRC has been started expanding field genebank coverage using these accessions.